2021
DOI: 10.1111/cns.13779
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet ameliorates cognitive impairment and neuroinflammation in a mouse model of Alzheimer’s disease

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 61 publications
2
45
1
Order By: Relevance
“…ED suppression can be attained with similar effect size and electrophysiological profile by small molecule ketone ester compounds that provide ketone bodies pharmacologically. These data provide a mechanistic understanding of earlier observations of visuo-spatial memory improvement with KD (Xu et al , 2022; Yin et al, 2016) or a ketone ester diet (Kashiwaya et al , 2013) in AD models. We are the first to show that KD reduces AD-induced epileptiform activity, providing a functional mechanism of action linked to rapid cognitive decline in AD patients (Lam et al, 2017; Vossel et al, 2013; Vossel et al, 2016) and with translational applicability in patients (Bakker et al, 2015; Bakker et al, 2012; Vossel et al, 2021; Vossel et al, 2017).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…ED suppression can be attained with similar effect size and electrophysiological profile by small molecule ketone ester compounds that provide ketone bodies pharmacologically. These data provide a mechanistic understanding of earlier observations of visuo-spatial memory improvement with KD (Xu et al , 2022; Yin et al, 2016) or a ketone ester diet (Kashiwaya et al , 2013) in AD models. We are the first to show that KD reduces AD-induced epileptiform activity, providing a functional mechanism of action linked to rapid cognitive decline in AD patients (Lam et al, 2017; Vossel et al, 2013; Vossel et al, 2016) and with translational applicability in patients (Bakker et al, 2015; Bakker et al, 2012; Vossel et al, 2021; Vossel et al, 2017).…”
Section: Discussionsupporting
confidence: 62%
“…Reports of the effect of KD or ketone bodies on Aβ deposition have been conflicting, with Aβ either reduced (Kashiwaya et al , 2013; Van der Auwera et al, 2005; Xu et al, 2022) or unchanged (Aso et al, 2013; Beckett et al, 2013; Brownlow et al, 2013). While changes in plaque accumulation could not explain the very rapid kinetics we observed for the effect of KD and ketone esters on epileptiform activity, we nevertheless carried out an exploratory immunohistochemical analysis of mice after 7 months on KD (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to a standard chow diet, APP/V717I transgenic mice fed a 43-day KD had a 25% reduction in brain Aβ levels ( Van der Auwera et al, 2005 ). Similarly, 5xFAD mice fed a 4-month KD had reduced hippocampal Aβ deposition compared to the standard chow diet ( Xu et al, 2021 ). Contrary to these findings, studies of a 16-week ( Brownlow et al, 2013 ) and 1-month ( Beckett et al, 2013 ) KD in APP/PS1 transgenic mice demonstrated improvements in motor function but not Aβ deposition; however, the APP/PS1 mice on the 1-month KD had decreases in brain and skeletal muscle CTF99 ( Beckett et al, 2013 ), the precursor for Aβ.…”
Section: Ketotherapies and Amyloid-βmentioning
confidence: 99%
“…Of note, elevations of Aβ have also been shown to stimulate pro-inflammatory cytokine expression by microglia, which may be more prominent in early stages of pathology while Aβ oligomers are still soluble rather than deposited into fibrillar plaques ( White et al, 2005 ; Sondag et al, 2009 ). The KD has also been shown to decrease inflammatory microgliosis in several models including the 5xFAD mouse model ( Xu et al, 2021 ).…”
Section: Ketotherapies and Amyloid-βmentioning
confidence: 99%
“…In a recent study, a ketogenic dietary intake for 4 months improved spatial and working memory and decreased amyloid plaque deposition and microglia activation in the AD mouse model 5XFAD [67]. Similarly, KD feeding for 1 month in APP/PS1 knock-in mice ameliorated their reduced motor performance, but their beta amyloid levels were unchanged in both brain and muscle [68].…”
Section: Nervous Systemmentioning
confidence: 93%